Artificial intelligence-estimated biological heart age using a 12-lead electrocardiogram predicts mortality and cardiovascular outcomes - Baek, Yong-Soo; Lee, Dong-Ho; Jo, Yoonsu; Lee, Sang-Chul; Choi, Wonik; Kim, Dae-Hyeok (Frontiers in Cardiovascular Medicine, 2023)
Background: There is a paucity of data on artificial intelligence-estimated biological electrocardiography (ECG) heart age (AI ECG-heart age) for predicting cardiovascular outcomes, distinct from the chronological age (CA). We developed a deep learning-based algorithm to estimate the AI ECG-heart age using standard 12-lead ECGs and evaluated whether it predicted mortality and cardiovascular outcomes. Methods: We trained and validated a deep neural network using the raw ECG digital data from 425,051 12-lead ECGs acquired between January 2006 and December 2021. The network performed a holdout test using a separate set of 97,058 ECGs. The deep neural network was trained to estimate the AI ECG-heart age (mean absolute error, 5·8 ± 3·9 years; R-squared, 0·7 [r=0·84, p<0·05]). Findings: In the Cox proportional hazards models, after adjusting for relevant comorbidity factors, the patients with an AI ECG-heart age of 6 years older than the CA had higher all-cause mortality (hazard ratio (HR) 1·60 [1·42–1·79]) and more major adverse cardiovascular events (MACEs) (HR 1·91 [1·66–2·21]), whereas those under 6 years had an inverse relationship (HR 0·82 [0·75–0·91] for all-cause mortality; HR 0·78 [0·68–0·89] for MACEs). Additionally, the analysis of ECG features showed notable alterations in the PR interval, QRS duration, QT interval and corrected QT Interval (QTc) as the AI ECG-heart age increased. Conclusion: Biological heart age estimated by AI had a significant impact on mortality and MACEs, suggesting that the AI ECG-heart age facilitates primary prevention and health care for cardiovascular outcomes.